HRD, OD, and institution building: essays in memory of Udai Pareek - Rao, T. V; Khandelwal, Anil K (New Delhi Atlantic, 2016)
Dr Udai Pareek, one of India$1 (Bs most influential social scientists of yesteryears, has changed the thought process of many organizations and individuals. He was fondly known as the (3z(BFather of HRD(3y (Bin India. In this book, leaders from both industry and academia give their original contributions in extending those of Dr Pareek$1 (Bs in HRD, OD, and institution building in India. The learnings from their experiences will serve as a valuable guide to leaders in all walks of life ranging from industry to education and social development. The book showcases Dr Pareek$1 (Bs contributions to HRD, OD, and institution building through the eyes of experts from the industry and academia.s
Keywords: Includes bibliographical references, notes and index; Personnel management; Organizational change